Enteritis in raccoons (Procyon lotor) caused by an infection with zoonotic Salmonella and carnivore parvovirus - Kristin Pütsch; Ingo Spitzbarth; Regina Scheller; Kristin Heenemann; Florian Hansmann (BMC Veterinary Research)
Abstract Background The raccoon (Procyon lotor) is a potential carrier of a large number of zoonotic pathogens, and its population is increasing in urban areas in Europe. In the present study, we investigated two cases of fatal enteritis in raccoons in Germany. Parvoviruses are a common cause of enteritis in raccoons, however in these cases an additional infection with zoonotic Salmonella was found, which has not yet been described in other countries than the United States. Case presentation Two female raccoons, aged 14 and 18 weeks, were submitted for necropsy. Histopathology of the small intestine revealed crypt degeneration and necrosis, atrophy and fusion of villi, as well as numerous bacteria partially covered by fibrinous pseudomembranes. By microbiological culture of small intestinal samples Salmonella enterica subsp. enterica Serovar Kottbus and Salmonella enterica subsp. enterica Serovar Ferruch were isolated, respectively. In addition, carnivore protoparvovirus type 1 was identified in the small intestine of both animals. Conclusions The infection of raccoons with carnivore protoparvovirus type 1 results in immunosuppression, which facilitates the spread of other pathogens. Both isolated Salmonella serovars represent a significant zoonotic threat for humans being in contact with the raccoon. Furthermore, in raccoons with sudden death a double infection with carnivore protoparvovirus type 1 and Salmonella should be considered as an important differential diagnosis.